Mentee perceptions of beneficence of faculty-centered academic mentoring: Reflections from a pilot program - Phiri, L.L. (South African Journal of Higher Education, 2020)
Three of the most notable changes that have radically changed the landscape of higher education in South Africa (SA) over the past decade relates to an increase in the student body, free education and a call for decolonisation of knowledge recently chartered by the #FeesMustFall movement in 2015. Academic mentoring can be seen as a reflexive praxis to some of the challenges that accompanies issues of formal and epistemological access in higher education in South Africa. This paper draws on the findings of a two-year pilot project (2015-2016) on academic mentoring within the faculty of engineering and building studies at the University of Johannesburg, South Africa. The paper reflects on the value of academic mentoring in facilitating student perceived academic success. The uniqueness of the paper is that it highlights the value of mentoring during transition in the first year at university and subsequent senior years of the student’s academic trajectory. A mixed-method methodology using an evaluation-based questionnaire was employed from a sample of 14 (n = 14) participants in their 1st to 4th year of study towards a bachelor’s degree in Engineering. Perspectives of mentees were examined in terms of their experiences of participation and how they benefited from mentoring academically and psychosocially. At a response rate of 77. 7%, the academic mentoring programme was experienced as being beneficial to mentees (86%). Psychosocial benefits such as an appreciation for diversity, networks, improved confidence and belonging were reported as gains. Among academic benefits were study skills (79%), assistance with difficult modules (79%) and improvement of academic performance (86%). Findings provide strong considerations in support of the expansion and continuity of academic mentoring programs in the faculty of engineering and building studies and the university at large. Academic mentoring is beneficial for all the stakeholders involved if it is done correctly.